2020
DOI: 10.3390/su12041408
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Photovoltaic Systems in Sacred Buildings for the Purpose of Electric Power Production: The Case Study of the Cathedral of St. Michael the Archangel in Belgrade

Abstract: In light of climate changes, technological development and the use of renewable energy sources are considered very important nowadays, both in newly designed structures and reconstructed historic buildings, resulting in the reduction in the commercial energy consumption and CO2 environmental emissions. This paper explores the possibilities of improving the energy efficiency of sacred heritage buildings by utilizing photovoltaic systems. As an exceptionally significant cultural good, the Cathedral of St. Michae… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 7 publications
0
10
0
9
Order By: Relevance
“…The comparison of interactivity between wired and wireless connections was briefed in [217,218]. According to the studies mentioned above, wireless connectivity or charging could achieve up to 65% connectivity, whereas conventional connectivity only achieved rates of 10% [219]. Several wireless communication devices have proven able to detect automatically and comply with V2G standards, helping to automate wireless charging.…”
Section: Ev-based Vehicle-to-grid (V2g)mentioning
confidence: 99%
“…The comparison of interactivity between wired and wireless connections was briefed in [217,218]. According to the studies mentioned above, wireless connectivity or charging could achieve up to 65% connectivity, whereas conventional connectivity only achieved rates of 10% [219]. Several wireless communication devices have proven able to detect automatically and comply with V2G standards, helping to automate wireless charging.…”
Section: Ev-based Vehicle-to-grid (V2g)mentioning
confidence: 99%
“…This can assist in reducing emissions of harmful gases and the dependence on fossil fuels. Additionally, it can increase the country's energy independence [30,43]. Furthermore, solar systems in households are frequently flexible and can be adapted to meet users' requirements, making them a well-liked choice for renewable energy.…”
Section: Solar Potential and Simulations Of Pv Solar Plantsmentioning
confidence: 99%
“…Sudimac et al [30] analyzed and concluded that applying photovoltaic systems in sacred heritage buildings in Serbia would reduce commercial energy consumption and CO 2 emissions into the environment and thereby improve ecological and economic sustainability. Žikić et al [31] surveyed 400+ respondents on the topic of energy production and renewable energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 These campaigns have had considerable success, leading to over 5500 churches having electrical energy generated from 100% renewable sources, 4 recently acknowledged in a study of mounting solar panels on the Cathedral of St. Michael the Archangel in Belgrade. 5 In most cases, the churches switched their electrical energy supplier to a supplier that only generates electrical energy through renewable energy sources. However, some churches went further by installing solar photovoltaic (PV) systems on their roofs, generating electrical energy from sunlight.…”
mentioning
confidence: 99%
“…In a model of the installation of a PV system on the Cathedral of St. Michael the Archangel in Belgrade, the software suite PVsyst combined with data on the annual solar radiation in Serbia identified the number of PV modules required to power its lighting. 5 Nina-Cristina et al described the practicalities of installing solar on a church in Romania, comparing PVsyst with a mathematical model developed at the Technical University of Cluj-Napoca, TUCN. They used local solar irradiation and ambient temperature data provided by TUCN.…”
mentioning
confidence: 99%